On-Site Protection Scheme for Microgrid with High Penetration Rate of Grid-Forming Inverter Interfaced Distributed Energy Resources - Yuan, Yubo; Li, Juan; Jiang, Yunlong; Xu, Sudi; Cao, Haiou (EAI Endorsed Transactions on Energy Web, 2025)
INTRODUCTION: Renewable energy represented by grid forming inverter interfaced distributed energy resources is increasingly connected to microgrids that can operate independently and have various modes, resulting in traditional relay protection schemes that cannot meet the requirements of protection selectivity and speed. OBJECTIVES: To this end, the fault characteristics of the grid forming distributed energy resources are analyzed. On this basis, the current, voltage and phase angle characteristics between them under the grid-connected/islanded operation mode of the microgrids are analyzed. METHODS: Aiming at the problem that the traditional protection loses selectivity, the phase angle difference between the pre-fault voltage and the post-fault current is used to judge the fault direction, and the internal fault acceleration factor of the integrated phase angle difference and the measured impedance is used to improve the action equation of the inverse time overcurrent protection. Aiming at the problem that the fault current is too small and the inverse-time overcurrent protection cannot be started when the two-phase short-circuit fault occurs in the islanded state, a low-voltage protection criterion based on the comprehensive phase angle difference characteristics is set up, and a microgrid protection scheme combining improved inverse-time over-current protection and low-voltage protection is obtained. RESULTS: The model is built by PSCAD, the theoretical analysis and simulation results show that the scheme can operate quickly and reliably in the grid-connected/islanded operation state of the microgrid. CONCLUSION: The results verify the effectiveness of the proposed protection scheme.